Microbial single-strand annealing proteins enable CRISPR gene-editing tools with improved knock-in efficiencies and reduced off-target effects. Issue 6 (22nd February 2021) - Wang, Chengkun; Cheng, Jason K W; Zhang, Qianhe; Hughes, Nicholas W; Xia, Qiong; Winslow, Monte M; Cong, Le
Abstract: Several existing technologies enable short genomic alterations including generating indels and short nucleotide variants, however, engineering more significant genomic changes is more challenging due to reduced efficiency and precision. Here, we developed RecT Editor via Designer-Cas9-Initiated Targeting (REDIT), which leverages phage single-stranded DNA-annealing proteins (SSAP) RecT for mammalian genome engineering. Relative to Cas9-mediated homology-directed repair (HDR), REDIT yielded up to a 5-fold increase of efficiency to insert kilobase-scale exogenous sequences at defined genomic regions. We validated our REDIT approach using different formats and lengths of knock-in templates. We further demonstrated that REDIT tools using Cas9 nickase have efficient gene-editing activities and reduced off-target errors, measured using a combination of targeted sequencing, genome-wide indel, and insertion mapping assays. Our experiments inhibiting repair enzyme activities suggested that REDIT has the potential to overcome limitations of endogenous DNA repair steps. Finally, our REDIT method is applicable across cell types including human stem cells, and is generalizable to different Cas9 enzymes.